2021
DOI: 10.1016/j.cub.2021.06.079
|View full text |Cite
|
Sign up to set email alerts
|

The spatiotemporal organization of experience dictates hippocampal involvement in primary visual cortical plasticity

Abstract: The spatiotemporal organization of experience dictates hippocampal involvement in primary visual cortical plasticity Highlights d Hippocampus is required for long-term plasticity in V1 elicited by visual sequences d Hippocampal damage impairs anticipatory activity when sequence elements are withheld d Hippocampus is required for V1 stimulus representations shaped by temporal context

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 83 publications
4
29
0
Order By: Relevance
“…In fact, we previously speculated that cue-triggered reactivation of simple sequences might be driven by an automatic pattern completion-like mechanism that reactivates all associated items based on partial input (Ekman et al, 2017). This idea is in line with the finding that predictive representations in V1 correlated with pattern completion-like activity in the hippocampus (Hindy et al, 2016;Kok & Turk-Browne, 2018) that might be driving V1 activity (Finnie et al, 2021;Ji & Wilson, 2007).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In fact, we previously speculated that cue-triggered reactivation of simple sequences might be driven by an automatic pattern completion-like mechanism that reactivates all associated items based on partial input (Ekman et al, 2017). This idea is in line with the finding that predictive representations in V1 correlated with pattern completion-like activity in the hippocampus (Hindy et al, 2016;Kok & Turk-Browne, 2018) that might be driving V1 activity (Finnie et al, 2021;Ji & Wilson, 2007).…”
Section: Discussionsupporting
confidence: 67%
“…On a conceptual level, navigation (in memory and space) and processing visual events both involve abstraction of the relational structure between events to enable forward planning and predictions. Similar to navigational space, visual space can be represented in terms of its relational structure like direction and distance, and it has been suggested that similar mechanisms might underlie spatial and non-spatial representations (Nau, Julian, et al, 2018), especially if there is sequential structure present (Finnie et al, 2021). Supporting this notion, recently, a conceptual link between representations for visual understanding and spatial navigation has been proposed that suggests a common underlying map-like representation of visual and navigational task structure (Schwartenbeck et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When first presented with an oriented grating stimulus, mice produce an easily measured visually evoked fidgeting behavior (Figure 2A) that subsides with increasing familiarity via a process we have termed orientation-selective habituation (OSH). With a similar degree of selectivity to SRP, OSH is reversed and movement re-emerges upon presentation of a novel stimulus (Figure 2B) Kaplan et al, 2016;Fong et al, 2020;Finnie et al, 2021). VEP recordings from these headfixed mice reveal that these behavioral changes occur along a comparable timecourse to SRP (Figure 2C).…”
Section: Orientation-selective Habituationmentioning
confidence: 82%
“…In fact, the structure of the adaptive subunit model suggests that this memory could be primarily encoded by synaptic and cellular variables of neurons within V1. At the same time, recent results have shown that responses in V1 can be influenced by activity in the hippocampus ( 77 , 78 ), so it would be premature to rule out any such involvement.…”
Section: Discussionmentioning
confidence: 99%